2016
DOI: 10.5194/bg-13-3091-2016
|View full text |Cite
|
Sign up to set email alerts
|

Microbial co-occurrence patterns in deep Precambrian bedrock fracture fluids

Abstract: The bacterial and archaeal community composition and the possible carbon assimilation processes and energy sources of microbial communities in oligotrophic, deep, crystalline bedrock fractures is yet to be resolved. In this study, intrinsic microbial communities from groundwater of six fracture zones from 180 to 2300 m depths in Outokumpu bedrock were characterized using high-throughput amplicon sequencing and metagenomic prediction. Comamonadaceae-, Anaerobrancaceaeand Pseudomonadaceae-related operational tax… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
93
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(106 citation statements)
references
References 81 publications
(108 reference statements)
12
93
1
Order By: Relevance
“…In addition, marker genes for methanogenesis have been previously detected throughout the drillhole water column (Nyyssönen et al, 2014; Purkamo et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, marker genes for methanogenesis have been previously detected throughout the drillhole water column (Nyyssönen et al, 2014; Purkamo et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Ad hoc studies have been carried out on the microbial ecology of gas storage aquifers in France for almost two decades (Basso et al ., ; Berlendis et al ., ; Aüllo et al ., ; Ranchou‐Peyruse et al ., ). While various microbial metabolisms have been highlighted in these ecosystems, some seem to play key roles in the functioning of the microbial communities, particularly sulfate‐reducing microorganisms (SRM) and methanogenic archaea, as already demonstrated for other subsurface environments (Itävaara et al ., ; Schrenk et al ., ; Purkamo et al ., ). Moreover, one of these studies targeting French gas storage aquifers suggested that CO 2 and H 2 could be the source of the functioning of the microbial communities located far away from the gas bubble in these oligotrophic environments (Basso et al, 2009), according to the Subsurface Lithoautotrophic Microbial Ecosystems principle (Stevens & McKinley, ; Pedersen, ; Chapelle et al ., ; Freund et al ., ; Lin et al ., ; Takai et al ., ; Crespo‐Medina et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen-using bacteria (called Dethiobacter) dominated our microcosms. Our previous study showed that these microbes are playing a big role in formation of the microbial community in deep bedrock [3]. These organisms were also found by another study describing microbial communities enriched from serpentinizing groundwater [4].…”
Section: Rockderived Hydrogen-a Snack For the Deep Microbesmentioning
confidence: 70%